Acute and subchronic toxicity study of the water extract from Harrisonia perforata Merr. in rats - Seewaboon Sireeratawong (2018)
The water extract from Harrisonia perforata Merr. was studied for acute and subchronic toxicities. The extract at a single dose of 5,000 mg/kg was administered orally to female and male rats (5 males, 5 females). After 14 days, signs and behavioral changes, mortality, gross and histopathological changes of internal organs were examined. The body weight of the male treated rats was significantly decreased when compared to the control group. The extract did not produce signs of toxicity. For the subchronic toxicity test, the extract at doses of 300, 600 and 1,200 mg/kg body weight were orally administered to rats daily for 90 days (10 males, 10 females). Observation of signs, behavior and health status showed no abnormality in the test groups as compared with the controls. However, the body weight of all male treated rats was significantly decreased when compared to the control group. At the end of the study, necropsy and histopathology examination were performed in all animals in the control group, the test groups and the satellite group in which the extract was discontinued for another 28 days. Body and organ weights, hematological and blood clinical chemistry were also examined. The results suggest that the water extract of Harrisonia perforata Merr. does not cause acute and subchronic toxicities in rats.